Total Quality Management and Public Administration – The case of Vila Real town hall - Patrocínia Ferreira; Francisco Diniz (European Regional Science Association (ERSA), 2004)
Nowadays, before starting any goods or service production process, one tries to learn something about their quality. This is an issue the customers segment is confronted with when choosing from the supply at one's disposal. The quality movement's main idea is that all goods and services must achieve a maximum quality. If one is to understand this movement first one has to be able to understand the implications of its assumptions in the production process and organization. (Connor, 1997). In most countries, public administration is the sector which carries the biggest weight upon employment and one supplying most goods and services. Therefore, it cannot ignore Total Quality Management (TQM) The Portuguese Government acknowledges that "presently quality is universally recognized and accepted as the client's satisfaction at adequate costs and that it became an imperative for all public organizations following the customers' growing awareness of their rights”(DL n. 166-A/99, May 13). Portuguese local public administration is facing the challenge of having to solve new and complex problems resulting from economic, social and technologic changes. It is the purpose of this paper to go into such questions as: how can TQM be implemented in a change context in Vila Real municipality? Are there limits or favourable conditions to that implementation?
Keywords: 330